(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Increases in the cost of living, known as inflation, and decreases in these costs, known asdeflation, are two extremes that may affect a country’s economy. Both inflation and deflation are effects ofthe same underlying monetary system. Since the economy may rapidly shift from one situation to theother in response to inflation and deflation, it is crucial to keep the two in check, Including a research thattalks about inflation, deflation, causes of deflation, the difference between inflation and deflation, andinflation and deflation rates throughout the world in 2022 in addition to the inflation rate in India.